Application of Sequence-Specific Labeled 16S rRNA Gene Oligonucleotide Probes for Genetic Profiling of Cyanobacterial Abundance and Diversity by Array Hybridization - Rudi, Knut (American Society for Microbiology, 2000)
DNA sequence information for the small-subunit rRNA gene (16S rDNA) obtained from cyanobacterial cultures was used to investigate the presence of cyanobacteria and their abundance in natural habitats. Eight planktonic communities developing in lakes characterized by relatively low algal biomass (mesotrophic) and in lakes with correspondingly high biomass (eutrophic) were selected for the study. The organismal compositions of the water samples were analyzed genetically, using multiplex sequence-specific labeling of oligonucleotide probes targeted to 16S rDNA and subsequent hybridization of the labeled probes to their respective complements spotted onto a solid support (DNA array). Ten probes were established to determine the relative abundances of the discernible cyanobacteria encountered in the selected lakes. The probes were generally specific for their targets, as determined through analyses of clone cultures. Reproducible abundance profiles were established for the lakes investigated in the subsequent analyses of natural cyanobacterial communities. The results from the genetic analyses were then compared with information obtained from standard hydrobiological and hydrochemical analyses. Qualitatively, there were relatively good correlations among the groups of organisms (Nostoc, Microcystis, and Planktothrix species) found in the different lakes. The levels of correlation were lower for the quantitative data. This may, however, be due to differences in sample processing technique. The conclusions from these comparisons are that the genetic abundance profiles may provide a foundation for separating and quantifying genetically distinct groups of cyanobacteria in their natural habitats.